Optimasi Human Error pada Proses Produksi Air Minum Dalam Kemasan di PT. Telaga Tanjung Pomosda Nganjuk - Irawan, Putut Ade; Lukmandono, Lukmandono (Universitas Kadiri, 2024)
PT. Telaga Tanjung Pomosda, a bottled mineral water manufacturer in Nganjuk, East Java, faces challenges in maintaining high production standards and addressing operational issues such as product rejection and production process errors, impacting overall company efficiency and reputation. This study identifies operational error factors and evaluates the effectiveness of improvement methods. Research procedures utilize HTA, SHERPA, and Poka-Yoke to identify and reduce human errors in bottled mineral water production at PT. Telaga Tanjung Pomosda Nganjuk, focusing on error analysis, probability assessment, and Poka-Yoke strategy implementation. The bottled water packaging process involves critical stages such as cup packaging, pressing, and packing. Errors in each stage can result in delays, decreased water volume, imperfectly pressed lids, and packing mistakes, hindering the entire production process. Research at PT. Telaga Tanjung Pomosda identifies operator issues in machine settings, water measurement, lid positioning, task interruptions, packaging, and cup positioning, with solutions including routine checks and training to enhance product quality